THE EFFECT OF SERVICE QUALITY, BRAND IMAGE AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY - Yusuf, Yusuf (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
The purpose of this study is to examine and explain the influence of service quality, brand image, and customer satisfaction on customer loyalty, both simultaneously and partially. Data collection was conducted using a structured questionnaire distributed to all customers. The population and sample of this study consisted of all 40 customers of PT. Mentari Mas Multimoda Kendari. The analytical tool used was multiple linear regression analysis with the assistance of SPSS software version 25. The results of the study indicate that, simultaneously, service quality, brand image, and customer satisfaction have a significant influence on customer loyalty. Partially: (1) Service quality has a positive and significant effect on customer loyalty, (2) Brand image has a positive and significant effect on customer loyalty, and (3) Customer satisfaction has a positive and significant effect on customer loyalty. These findings indicate that enhancing these three variables is crucial in building customer loyalty for the company. Practical implications suggest that management should focus on optimizing service quality and strengthening brand image. Limitations of the study include a small sample size & a geographically limited scope restricted to Kendari City